2003
DOI: 10.2169/internalmedicine.42.1077
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence that Sustained Dysfunction of Left Atrial Appendage Contributes to the Occurrence of Cardiogenic Brain Embolism in Patients with Paroxysmal Atrial Fibrillation

Abstract: Objective The goal of this study was to investigate transesophageal echocardiographic (TEE) findings after the termination of atrial fibrillation to clarify the direct evidence for occurrence of acute cardiogenic brain embolism (CBE) in patients with paroxysmal atrial fibrillation (PAF).Patients and Methods Among98 consecutive patients with CBE, we investigated TEE in 16 patients with PAF (Group CBE, 72±10 years) within 7 days of the onset and 2 weeks after the first study, in comparison with 15 agematched PAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
(9 reference statements)
1
12
1
Order By: Relevance
“…Since TEE provides a high-resolution image of the left atrium for evaluating the severity of blood stasis in the LAA, dense LASEC and reduced LAAPV on TEE can be a marker of throm-boembolism in AF patients (14,18,19). Therefore, TEE findings are useful for evaluating the risk of cardioembolic stroke in patients with AF.…”
Section: Laapvmentioning
confidence: 99%
“…Since TEE provides a high-resolution image of the left atrium for evaluating the severity of blood stasis in the LAA, dense LASEC and reduced LAAPV on TEE can be a marker of throm-boembolism in AF patients (14,18,19). Therefore, TEE findings are useful for evaluating the risk of cardioembolic stroke in patients with AF.…”
Section: Laapvmentioning
confidence: 99%
“…10 The present results indicate that prolonged AEMI is not only a predictor of AF episodes but also a predictor of CE in patients with PAF. 25 Second, prolongation of AEMI per se might be associated with alterations in the atrial endocardium, which facilitates thrombus formation, independently from PAF episodes. First, longer AEMI might reflect more frequent and/or longer PAF episodes, which would compromise anticoagulant barrier of the atrial endocardium 24 and reduce the peak flow velocity and fractional area change in LA appendage.…”
Section: Discussionmentioning
confidence: 99%
“…Beinart et al reported an independent predictive value of LAA dimensions for embolic cerebral events in a study with 144 patients [10]. Considering the well established association between reduced LAA emptying velocities and thrombus formation in the LAA, VENC-CMR could be an attractive adjunctive non-invasive tool in this context [1,2]. A comprehensive CMR protocol including measurements of LA fibrosis, LAA dimensions and passive LAA emptying velocities could potentially improve risk stratification in patients with AF [8-11].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombus formation is promoted by an impaired LAA function with reduced emptying of the LAA [2]. An impaired LAA function is typically related to atrial fibrillation (AF).…”
Section: Introductionmentioning
confidence: 99%